Syntheses, crystal structures, and magnetic properties of metal-organic hybrid materials of Co(II) using flexible and rigid nitrogen-based ditopic ligands as spacers - Ahmad, Musheer; Sharma, Mamsh K.; Das, Raja; Poddar, Pankai; Bharadwaj, Parimal K. (Crystal Growth & Design, 2012)
{A carboxylate-based flexible ligand, 5-(4-carboxybenzyloxy)isophthalic acid (p-cbiaH(3)), readily reacts with Co(II) salts in the presence of different pyridine-based coligands such as 4-bis(4-pyridinylmethyl)piperazine (bpmp) or 1,2-di(4-pyridyl)ethylene (dpe) under hydrothermal conditions to afford two different three-dimensional (3D) coordination polymers, {[Co-4(OH)(2)(p-cbia)(2)(bpmp)-(H2O)(3)]center dot 2H(2)O}(n) (1) and {[Co-4(OH)(2)(p-cbia)(2)(dpe)(H2O)(4)]center dot 2H(2)O\